السودان والثورة الجزائرية (1954-1962) - فتيحة بعرة (جامعة محمد بوضياف بالمسيلة, 2025)
خلال منتصف القرن العشرين، لعبت حركات التحرر الوطني دورًا محوريًا في تشكيل وعي الشعوب وإعادة صياغة الخارطة السياسية في العالم العربي والإفريقي. وفي هذا السياق، برزت الثورة الجزائرية (1954-1962) كأحد أبرز النماذج الكفاحية ضد الاستعمار، وتفاعلت معها دولة السودان، التي نالت استقلالها (1956) في خضم هذه التحولات، حيث قدمت دعمًا متنوعًا وسجلت تأثرًا متبادلاً عكس عمق الروابط النضالية والتاريخية. ساهم السياق التاريخي للسودان كدولة حديثة الاستقلال، والتزامه بمبادئ التضامن العربي والإفريقي، في تمكينه من تقديم أشكال متعددة من الدعم للثورة الجزائرية. شمل هذا الدعم المواقف السياسية والدبلوماسية الرسمية، والتعبئة الشعبية والإعلامية الواسعة، بالإضافة إلى محاولات تقديم مساندة مادية ولوجستية رغم التحديات. وفي المقابل، أثرت الثورة الجزائرية على الوعي السياسي والتوجهات الفكرية في السودان، وعززت من روح التحرر والتطلع نحو دور إقليمي فاعل. أدى هذا التفاعل إلى تعزيز مكانة القضية الجزائرية على الساحة الدولية، وفتح آفاقًا جديدة للتضامن بين الدول حديثة الاستقلال، وشكّل نموذجًا للعلاقات بين دول تسعى للتحرر وبناء الذات. لم يقتصر تأثير هذا التفاعل على الجانب الرسمي، بل امتد ليشمل الوجدان الشعبي والمثقفين في كلا البلدين، ورسخ قناعات مشتركة حول أهمية النضال من أجل السيادة والكرامة. بفضل هذا التفاعل متعدد الأوجه، تمكن السودان من تأكيد دوره كقوة داعمة لحركات التحرر في المنطقة، وساهمت الثورة الجزائرية في إلهام قطاعات واسعة من الشعب السوداني وقواه السياسية. وبهذا، أسهمت هذه العلاقة بشكل كبير في إثراء وتجديد خطاب التحرر الوطني والتضامن الإقليمي خلال تلك الفترة الحاسمة من تاريخ البلدين والعالمين العربي والإفريقي. During the mid-20th century, national liberation movements played a pivotal role in shaping the consciousness of peoples and redrawing the political map in the Arab and African world. In this context, the Algerian Revolution (1954-1962) emerged as one of the most prominent examples of struggle against colonialism. The state of Sudan, which gained its independence in 1956 amidst these transformations, interacted with this revolution, providing diverse support and registering mutual influence that reflected the depth of their shared struggle and historical bonds. Sudan's historical context as a newly independent state, coupled with its commitment to the principles of Arab and African solidarity, enabled it to offer multifaceted forms of support to the Algerian Revolution. This support encompassed official political and diplomatic stances, widespread popular and media mobilization, in addition to attempts at providing material and logistical assistance despite the challenges. Conversely, the Algerian Revolution influenced political consciousness and intellectual currents in Sudan, reinforcing the spirit of liberation and the aspiration for an active regional role. This interaction led to the enhancement of the Algerian cause's standing on the international stage, opened new horizons for solidarity among newly independent nations, and served as a model for relations between states striving for liberation and self-determination. The impact of this engagement was not limited to the official sphere but extended to popular sentiment and intellectuals in both countries, cementing shared convictions about the importance of the struggle for sovereignty and dignity. Thanks to this multifaceted interaction, Sudan was able to consolidate its role as a supportive force for liberation movements in the region, while the Algerian Revolution inspired broad segments of the Sudanese populace and its political forces. Thus, this relationship significantly contributed to enriching and renewing the discourse of national liberation and regional solidarity during that critical period in the history of both nations and the Arab and African worlds.